Gamification in Software Testing: A Characterization Study - Jesus, Gabriela Martins de; Ferrari, Fabiano Cutigi; Porto, Daniel de Paula; Fabbri, Sandra Camargo Pinto Ferraz (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2018: Anais do III Simpósio Brasileiro de Testes de Software Sistemático e Automatizado, 2018)
Context: Testing is a fundamental activity in the software development cycle. Revealing software faults is its main objective. Despite that, testing is considered unpleasant, dull and tedious. As a result, there is a lack of expertise among professionals while many projects fail. Gamification is a promising way to address testing issues; it is a new trend being used mostly to increase motivation, engagement and performance with the use of game elements in non-game contexts. Objective: To describe results of a study that aimed to characterize how gamification has been explored to support software testing. Method: The studies that compose our baseline for analysis and discussion were obtained through a systematic mapping carried out following a research protocol. To retrieve relevant literature, we applied automatic search and backward snowballing. At the end, we selected 15 studies that we analyzed and classified according to six perspectives: application context, used gamifcation elements, gamification goals, testing techniques, testing levels, and testing process phases. Results: The most used gamification elements are points, leader boards, and levels, and unit testing and functional testing are the level and technique most addressed in the studies, respectively. Conclusion: Gamification is a rising research topic, especially in the software testing field. The increasing interest for gamification has the potential do lead to positive outcomes. The map presented in this paper can be a useful resource for the identification of gaps and for triggering new research initiatives.